ARE ONLINE GUEST REVIEWS USEFUL? IMPLICATIONS FOR THE HOTEL MANAGEMENT - BĂLTESCU, Codruța Adina (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 18 (2016): Annales Universitatis Apulensis Series Oeconomica, 2016)
The technological progress and the development of communication means are factors that led to major changes in the hotel guests’ booking behavior. The official hotel ratings are no longer sufficient in the attempt to book a hotel. The modern consumer is equally interested in the opinions expressed by previous guests. The online reviews reflect assessments based on the travelers' personal experience and gain significant importance for other guests. This article presents an analysis of the accommodation offer located in the central area of Brașov municipality, and a synthesis of the assessments of Romanian and foreign tourists on Booking.com for the analyzed accommodation units. Moreover, considering that online guest reviews are useful both for the future customers (being a barometer of previous consumers' experiences) and also for managers (as an expression of opinions and expectations of guests) a conjoint analysis has been presented. The conjoint analysis explores the importance value of each hotel attribute score based on each individual’s ratings on the attributes and overall ratings.